2018
DOI: 10.31231/osf.io/cd7qv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How does mindfulness training improve moral cognition: A theoretical and experimental framework for the study of embodied ethics

Abstract: Mindfulness meditation has been primarily studied within the context of individual’s psychological well being and/or in relation to it’s potential to enhance cognitive skills such as attention and working memory. However, in Buddhism, mindfulness is used as a tool to cultivate wholesome actions, and as a means to promote virtuous, prosocial qualities. In this article, we postulate that heightened awareness of physiological and mental phenomena following mindfulness training may contribute to altered processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…49,50 Cultivating mindfulness-based skills is important in the process of moral discernment and helps clinicians address moral adversity and develop mediation pathways for emotional competency, cognitive function, and ethical action. 15,[49][50][51][52] Cultivating mindful awareness and cognitive skills aimed at recognizing, analyzing, and responding to ethical challenges and at fostering moral resilience holds promise for nursing ethics education. 53…”
Section: Mindfulnessmentioning
confidence: 99%
“…49,50 Cultivating mindfulness-based skills is important in the process of moral discernment and helps clinicians address moral adversity and develop mediation pathways for emotional competency, cognitive function, and ethical action. 15,[49][50][51][52] Cultivating mindful awareness and cognitive skills aimed at recognizing, analyzing, and responding to ethical challenges and at fostering moral resilience holds promise for nursing ethics education. 53…”
Section: Mindfulnessmentioning
confidence: 99%
“…In particular, the authors postulate a theory which highlights the interrelation between the ethical beliefs of the individual and his relationship to the environment; cultivating internal and external awareness seems to arouse a process of ethics embodied in moral cognition. In fact, the changes reported by literature in MBI participants involve a meta-awareness and a different perspective of the self, probably influencing the processing of morally-relevant situations and stimuli thus encouraging moral action (Sevinc and Lazar, 2019 ). However, HCPs often suffer from psychological distress and therefore experience a varied spectrum of symptoms related to this condition.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence showed that mindfulness has a close relationship with social cognition. For example, research revealed that mindfulness training improved various social cognitive abilities such as social contact (Lindsay et al, 2019), affective social cognition and social functioning (Mediavilla et al, 2021), mental state attribution and empathic concern (Tan et al, 2014), cognitive empathy (Winning & Boag, 2015), and moral cognition (Sevinc & Lazar, 2019). As a result, mindfulness training is shown to be an effective way to improve social cognition.…”
Section: Introductionmentioning
confidence: 99%